A Review of Psoriasis, a Known Risk Factor for Cardiovascular Disease and Its Impact on Folate and Homocysteine Metabolism - Ian McDonald; Maureen Connolly; Anne-Marie Tobin (Journal of Nutrition and Metabolism)
Psoriasis is a chronic inflammatory skin condition with an increased risk of cardiovascular disease. This risk has been attributed to an association with many independent risk factors including obesity, hypertension, smoking, and dyslipidemia. Psoriasis patients also have lower levels of folate and conversely higher levels of homocysteine, which in itself is a risk factor for cardiovascular disease. It has been postulated that low folate levels in this group may be a direct cause of hyperhomocysteinemia and therefore a treatable risk factor by folate supplementation. This paper looks at the literature published to date on the relationship between psoriasis, homocysteine, and folate levels.